PERAN MAHASISWA KAMPUS MENGAJAR DALAM MENINGKATKAN KEMAMPUAN LITERASI DAN NUMERASI PESERTA DIDIK SEKOLAH DASAR INPRES LISABHETO - Mitak, Marsalina; Fitrah, F; Ice, Yuli (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2023)
The teaching campus program is a form of implementation of the MBKM (Merdeka Belajar – Kampus Merdeka) program from the Ministry of Cultural Education, Research and Technology. This program is intended for students in universities to contribute to advancing basic education. This teaching campus activity includes literacy and numeracy activities although in the teaching campus program there are two other focuses of activities, namely technology adaptation and school administration. Based on this, the purpose of the research conducted was to improve the numeracy literacy skills of grade III students at Inpres Lisabheto Elementary School. The type of research carried out is qualitative with a descriptive method. Data are collected through observation techniques and documentation during the activity. The results showed that the teaching campus program brings benefi